Dysregulation of mitochondrial function and biogenesis modulators in adipose tissue of obese children - Zamora-Mendoza, R.; Rosas-Vargas, H.; Ramos-Cervantes, M. T.; García-Zúñiga, P.; Pérez-Lorenzana, H.; Mendoza-Lorenzo, Patricia; Miliar-García, A.; Lara-Padilla, E.; Estrada Mena, Francisco Javier; Ceballos, Guillermo; Rodríguez, Alonso; Villarreal, Francisco J.; et al. (My University, 2017)
Background/Objectives: We aimed to evaluate mitochondrial biogenesis (MB), structure, metabolism and dysfunction in abdominal adipose tissue from male pediatric patients with obesity. Subjects/Methods: Samples were collected from five children with obesity (percentile ⩾95) and five eutrophic boys (percentile ⩾5/⩽85) (8–12 years old) following parental informed consent. We analyzed the expression of key genes involved in MB (sirtuin-1 (SIRT1), peroxisome proliferator-activated receptor-γ (PPARγ), PPARγ coactivator-1α (PGC1α), nuclear respiratory factors 1 and 2 (NRF1, NRF2) and mitochondrial transcription factor A (TFAM) and surrogates for mitochondrial function/structure/metabolism (porin, TOMM20, complex I and V, UCP1, UCP2, SIRT3, SOD2) by western blot. Citrate synthase (CS), complex I (CI) activity, adenosine triphosphate (ATP) levels, mitochondrial DNA (mtDNA) content and oxidative stress end points were also determined.